2008
DOI: 10.1002/app.28512
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) properties as a consequence of poly(butylene adipate‐co‐terephthalate) blending and acetyl tributyl citrate plasticization

Abstract: This study was aimed at the modulation of poly(lactic acid) (PLA) properties by the addition of both a low-molecular-weight plasticizer, acetyl tributyl citrate (ATBC), and a biodegradable aliphatic-aromatic copolyester, poly(butylene adipate-co-terephthalate) (PBAT). PLA/PBAT, PLA/ATBC, and PLA/PBAT/ATBC mixtures with 10-35 wt % ATBC and/or PBAT were prepared in a discontinuous laboratory mixer, compression-molded, and characterized by thermal, morphological, and mechanical tests to evaluate the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 37 publications
5
81
0
Order By: Relevance
“…I is achieved when the content of plasticizer is the highest. This effect is in contrast with the trend observed for the use of only a plasticizer in PLA, because usually the crystallinity developed during rapid cooling increases by increasing the plasticizer content [16,29,30]. In this case is the heterogeneity introduced by the plasticizer in nucleating crystals.…”
Section: Thermal Propertiesmentioning
confidence: 69%
See 2 more Smart Citations
“…I is achieved when the content of plasticizer is the highest. This effect is in contrast with the trend observed for the use of only a plasticizer in PLA, because usually the crystallinity developed during rapid cooling increases by increasing the plasticizer content [16,29,30]. In this case is the heterogeneity introduced by the plasticizer in nucleating crystals.…”
Section: Thermal Propertiesmentioning
confidence: 69%
“…The addition of the plasticizer resulted in a decrease in glass transition temperature of PLA. However the addition of increasing amount of PBAT resulted in an increase in PLA glass transition temperature as a consequence of preferential migration of ATBC in the PBAT phase [16] and a general synergistic effect was evidenced on the overall crystallization rate of the PLA component when both PBAT and ATBC were added to PLA. In the industrial production usually PLA is melt processed and then rapidly cooled [2] below its glass transition temperature.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…PLA have been blended with rubbers [3], thermoplastic starch (TPS) [4][5][6][7][8][9], poly(butylene succinate) (PBS) [10], poly(butylene succinate adipate) (PBSA) [11], poly(butylene adipateco-terephthalate) (PBAT) [12][13][14][15], acrilontryl-butadienestyrene (ABS) [16], polypropylene (PP) [17][18][19], and polystyrene (PS) [20,21], to obtain materials with lower cost and improved properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of Xiao et al [ 10 ] have shown that the addition of triphenyl phosphate as a plasticizer increases the spherulitic growth rate of PLA, as well as decreases the equilibrium melting temperature ( T m 0 ) as an effect of the plasticization of the chains. Previous work of Coltelli et al [ 1 ] showed the plasticizing effect of acetyl tributyl citrate (ATBC), which can induce a decrease in T g and an improvement in the mechanical properties of PLA/PBAT blends.…”
mentioning
confidence: 99%